Penyuluhan Resiko Jatuh Pada Lansia Di Masyarakat Pudak Payung - Widya Ervianta; Lilik Sigit Wibisono; Fitratun Najizah; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
One way to improve the quality of life for the elderly is to do physical exercise. Physical exercise can maintain or improve flexibility, cardiopulmonary endurance, agility, strength and balance. Several studies show that physical exercise has a consistent effect in reducing the risk of falls in healthy older adults. Kuptniratsaikul's research in 2009-2010 showed that simple balance exercises carried out by elderly people with a history of falls could reduce the incidence of falls in the elderly and significantly improve body balance. A 2017 Cuevas meta-analysis study showed that balance training programs showed the greatest effect in reducing the risk of falls in the elderly. For elderly people who are not yet able to do balance exercises independently, they need assistance from professional staff. Elderly people are an age group that is vulnerable to falls. The aim of implementing this service is to detect the risk of falls in the elderly and provide assistance with balance exercises as an effort to prevent the risk of falls in the elderly. Falls occur due to an unintentional loss of balance which results in failure of postural stability, or an unexpected and sudden change which results in the position landing on the floor . Associated risk factors include current health status (living in the community, nursing home, hospital, weak or active state), existing diseases (diabetes, hip fracture, stroke) and general changes related to aging (decreased balance, coordination, strength muscle, visual disturbances, etc.). The output targets to be achieved include publication of accredited national journals and copyright for videos of community service activities. The method used is a fall risk detection examination using the Time Up and Go Test and continued by providing balance training, so that elderly people who are at risk of falling can be identified as early as possible so that providing balance training can maintain and improve the elderly's body balance.